FIT FOR PURPOSE WELL CONTROL EQUIPMENT SELECTION FOR WORKOVER AND WELL SERVICE RIGS THROUGH DECISION MAKING APPROACH (CASE STUDY: PT BEI) - Devid Devid (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2021)
PT BEI is a subsidiary of Bravo Corporation that holds 100 percent-owned and operated interest in Rocka PSC. PT BEI need to improve the flexibility of its workover and well service rigs to be operated across the operating areas to deal with dynamic business plan and rig allocation as a strategy in entering the transition period to the end of concession of Rocka PSC. Well Control equipment associated with the rig contract Scope of Work (SOW) is identified as the main potential causes of why current rigs have less flexibility. A decision-making approach is utilized to find the solution. Well data mapping combined with existing business process and applicable standards review are conducted to determine the minimum Well Control equipment requirement, selection criteria and alternatives. The Analytic Hierarchy Process (AHP) is utilized as the decision-making method to analyze the alternatives. As the result, a BOP Class II A1-R1 (Annular + Blind-Shear ram) is selected as the fit for purpose Well Control equipment. The solution implementation improves the rig flexibility and saves potential 90,000 investment cost per rig for the rig contractors and 77,000 cost avoidance per rig for PT BEI.